The definitive guide to ARM Cortex-M3 and Cortex-M4 processors - Yiu, Joseph (Newnes, 2013)
This book presents the background of the ARM architecture and outlines the features of the processors such as the instruction set, interrupt-handling and also demonstrates how to program and utilize the advanced features available such as the Memory Protection Unit (MPU). Chapters on getting started with IAR, Keil, gcc and CooCox CoIDE tools help beginners develop program codes. Coverage also includes the important areas of software development such as using the low power features, handling information input/output, mixed language projects with assembly and C, and other advanced topics. Two new chapters on DSP features and CMSIS-DSP software libraries, covering DSP fundamentals and how to write DSP software for the Cortex-M4 processor, including examples of using the CMSIS-DSP library, as well as useful information about the DSP capability of the Cortex-M4 processorA new chapter on the Cortex-M4 floating point unit and how to use itA new chapter on using embedded OS (based on CMSIS-RTOS), as well as details of processor features to support OS operationsTopics on software porting from other architecturesA full range of easy-to-understand examples, diagrams and quick reference appendices.